2010
DOI: 10.1021/jp105652c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt on the Lower Critical Solution Temperature of Poly (N-Isopropylacrylamide)

Abstract: Classical molecular dynamics simulations were performed to investigate the effects of salt on the lower critical solution temperature (LCST) of Poly (N-isopropylacrylamide) (PNIPAM). PNIPAM is often studied as a protein proxy due to the presence of a peptide bond in its monomer unit. PNIPAM is a temperature sensitive polymer which exhibits hydrophobic-hydrophilic phase transition at its LCST. The presence of salt in the solution will shift its LCST, typically to a lower temperature. This LCST shift follows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
259
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(286 citation statements)
references
References 46 publications
26
259
1
Order By: Relevance
“…In other words, above the LCST, the PNIPAM molecules have smaller average extent [19]. For the endgrafted chains in our system, we observe the LCST around or slightly below 305 K; a value which coincides reasonably well with available experimental data [18,[31][32][33][34][35] and other simulation results of free PNIPAM chains [19,24,[36][37][38][39].…”
Section: Behavior Of the Nanoengine As A Function Of Temperaturesupporting
confidence: 90%
See 1 more Smart Citation
“…In other words, above the LCST, the PNIPAM molecules have smaller average extent [19]. For the endgrafted chains in our system, we observe the LCST around or slightly below 305 K; a value which coincides reasonably well with available experimental data [18,[31][32][33][34][35] and other simulation results of free PNIPAM chains [19,24,[36][37][38][39].…”
Section: Behavior Of the Nanoengine As A Function Of Temperaturesupporting
confidence: 90%
“…All molecular dynamics (MD) simulations have been performed with the LAMMPS software [22] developed at Sandia National Laboratories using the AMBER 94 force field [23,24] for PNIPAM and the TIP3P model for water [25]. The force field applied for the graphene has been used before for the thermal conductivity calculations of carbon nanotubes and graphene layers by one of the authors [26,27].…”
Section: Computational Methods and Simulation Detailsmentioning
confidence: 99%
“…Gangemi et al further extended the study carried out by Longhi et al by increasing the simulation length and by studying PNIPAM oligomer as well as two oligomers of PNIPAM having N-methacryloyl-L-valine and N-methacryloyl-L-leucine comonomers. 36 Gangemi 29 In their study, they carried out simulations of PNIPAM in 1 M of NaCl, NaBr, NaI, and KCl to elucidate the effects of different salt ions on the LCST of PNIPAM. Du et al found that cations have a much stronger affinity with the polymer, whereas anions bind weakly with the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of salts on the LCST of PNIPAm have been studied with a variety of measurement methods, such as cloud-point measurement [12], differential-scanning calorimetry [13], and a temperature-gradient microfluidic apparatus together with dark-field microscopy [14]. Furthermore, calculations with computational molecular dynamics simulations have been carried out [15]. LCST of PNIPAm as a function of molecular weight [16] and on that of PNIPAm microgel particles [17] have also been studied.…”
Section: Introductionmentioning
confidence: 99%